Design of Environment Monitoring System on Shipbuilding Outdoor. Issue 1 (1st January 2022) - Liu, Caiyun; Zhu, Dapeng; Shi, Shouchuang; Teng, Li; Ding, Yong; He, Jiajian
Abstract: Shipbuilding painting is the key part of hull construction outfitting and painting integration. General section painting, dock painting and terminal painting, are collectively referred to as shipbuilding outdoor painting, which is one of the major sources of pollution for ship building and repair because of its fugitive emission and volatile. In this paper, the environmental monitoring tasks of outfield painting are summarized based on the analysis of the current situation of industry monitoring. The key technologies such as communication and wiring, identification and conversion of heterogeneous data are broken through, and the environmental monitoring system for shipbuilding outdoor painting is built. The emission monitoring threshold was determined by combing relevant national/industry standards. The system implementation scheme is designed to provide a feasible scheme for green shipbuilding and repair, and promote the transformation and upgrading of the shipbuilding industry.